2020
DOI: 10.1093/scan/nsaa090
|View full text |Cite
|
Sign up to set email alerts
|

Shared and distinct functional networks for empathy and pain processing: a systematic review and meta-analysis of fMRI studies

Abstract: Abstract Background Empathy for pain is a complex phenomenon incorporating sensory, cognitive and affective processes. Functional neuroimaging studies indicate a rich network of brain activations for empathic processing. However, previous research focused on core activations in bilateral anterior insula (AI) and anterior/anterior mid-cingulate cortex (ACC/aMCC) which are also typically presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 80 publications
5
50
2
3
Order By: Relevance
“…Notably, the anterior insula cortex plays a complex role in processes directly or indirectly related to the acute and chronic pain experience, including pain empathy (Fallon et al, 2020; Xu et al, 2020b; Zhou et al, 2020), interoception and salience processing (Yao et al, 2018; Li et al, 2018) as well as emotional experience (Gogolla, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the anterior insula cortex plays a complex role in processes directly or indirectly related to the acute and chronic pain experience, including pain empathy (Fallon et al, 2020; Xu et al, 2020b; Zhou et al, 2020), interoception and salience processing (Yao et al, 2018; Li et al, 2018) as well as emotional experience (Gogolla, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Converging evidence from functional neuroimaging and lesion studies indicate that the temporoparietal junction (TPJ), which is situated at the posterior superior temporal sulcus (pSTS), and medial prefrontal cortex (mPFC) are essential for detecting and representing mental states of others, and play an important role in cognitive empathy and moral cognition ( Decety and Lamm, 2007 , Gallagher and Frith, 2003 , Lamm et al, 2007 , Moll et al, 2007 , Saxe et al, 2004 , Silani et al, 2013 , Yoder and Decety, 2014a ). In healthy participants, viewing others in pain reliably elicits response in dorsal anterior cingulate (dACC) and anterior insula (aINS; Decety et al, 2013a , Fallon et al, 2020 , Lamm et al, 2011 ), core nodes of the salience network which integrate multiple stimuli to coordinate cortical and subcortical resources to respond to motivationally relevant stimuli ( Decety, 2011 , Harsay et al, 2012 , Shackman et al, 2011 , Yoder and Decety, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that when observing others in pain, brain regions involved in the processing of self‐directed pain were also activated, but this mainly included parts of the affective‐motivational component of pain processing, such as the anterior mid‐cingulate cortex (aMCC) and the anterior insula (AI) (Botvinick et al., 2005; Lamm et al., 2011; Singer et al., 2004). Recent meta‐analytic research has revealed additional activations shared by empathy for pain and self‐direct pain in the inferior frontal gyrus and supramarginal gyri (Fallon et al., 2020). Besides, another meta‐analysis research demonstrated that the core neural empathy network (aMCC and AI) was activated when observing others in painful states as well as in nonpain negative affective states (Timmers et al., 2018).…”
Section: Introductionmentioning
confidence: 99%